Local Wisdom of Balinese People Managing Water in Tirta (Holy Water) Concept - I Nengah Muliarta; I Wayan Suanda; Ni Luh Suriani (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2021)
Water is a source of life on the surface of the earth because it becomes a necessity for every organism. The need for water continues to increase, but the availability of clean water continues to decrease. Efforts to preserve important water sources are made to meet current and future water needs. Hindus in Bali have long practiced water resources conservation and managing water quality through various forms of local wisdom. Local wisdom is passed down through generations of routine activities in daily life. Water as a gift because it gives life is placed as a holy one which is then referred to as holy water or tirta. The use of tirta in various ceremonial activities causes Hinduism in Bali to be often identified with tirta religion. For Balinese people, water is a symbol of Vishnu which is a manifestation of God as the preserver of world life. Positioning water as a sacred thing has the meaning of obligation to maintain the quality and quantity of water to be maintained. Positioning the water source as a sacred area is also a form of effort to protect the springs to avoid pollution. The ceremony of mendak tirta and mendak toya became a form of local wisdom on the procedures of water use and efficient use of water. The concept of nyegara-Gunung (sea-mountain) is one of the proofs that Balinese Hindus commit to maintaining the hydrological cycle, so that life is maintained.